2021
DOI: 10.1002/bse.2694
|View full text |Cite
|
Sign up to set email alerts
|

Offering flexible working opportunities to people with mental disabilities: The missing link between sustainable development goals and financial implications

Abstract: A global response to Covid-19 pandemic has triggered issues related to stress and social restrictions; thus, mental health is seen as a particular area of concern for social well-being for both policymakers and corporate regulators/companies. Given that mental health intersects with most, if not all, of the 17 sustainable development goals (SDGs), this research brought to light issues surrounding employment of people with mental disabilities (PWMDs) and the financial merits of employing them. An online survey … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 46 publications
0
10
0
Order By: Relevance
“…Mental health is a top priority in the world, as the cost of mental illness is more than 4% of GDP (Izutsu et al, 2015 ). Its importance stemmed from the intersection of mental health issues with all SDGs, and the rights of people with mental health disorders are denoted mainly in SDG-4, SDG-8, SDG-10, and SDG-11(Warmate et al, 2021 ). Achdut and Refaeli ( 2020 ) in a study to assess the unemployment and psychological distresses during the crisis of the COVID-19 pandemic concluded that the pandemic and the associated economic crisis posed significant threats to young people mental health.…”
Section: Resultsmentioning
confidence: 99%
“…Mental health is a top priority in the world, as the cost of mental illness is more than 4% of GDP (Izutsu et al, 2015 ). Its importance stemmed from the intersection of mental health issues with all SDGs, and the rights of people with mental health disorders are denoted mainly in SDG-4, SDG-8, SDG-10, and SDG-11(Warmate et al, 2021 ). Achdut and Refaeli ( 2020 ) in a study to assess the unemployment and psychological distresses during the crisis of the COVID-19 pandemic concluded that the pandemic and the associated economic crisis posed significant threats to young people mental health.…”
Section: Resultsmentioning
confidence: 99%
“…Tekeli-Yesil and Kiran (2020), however, have argued that nonstandard employment and its trade-offs should be considered specifically and significantly in hospital emergency and disaster planning. In the context of the COVID-19 pandemic, workers with mental disabilities have no flexible working opportunities (Warmate et al 2021). Organisations have used a flexible group-skunkworks approach to address technological difficulties, which has been very necessary for dealing with emerging HR-related challenges during the pandemic (Biron et al 2020).…”
Section: Flexible Workforcementioning
confidence: 99%
“…Vulnerable groups of labourers also require attention from both organisations and government. Although equal rights were practiced well in the pre-COVID-19 workforce, more support is needed for vulnerable groups of labourers during the pandemic (Warmate et al 2021). Employers can enjoy financial benefits for hiring workers with mental disabilities; at the same time, governments should develop effective policies to encourage the recruitment of workers with mental disabilities.…”
Section: Flexible Workforcementioning
confidence: 99%
“…Finally, although this article focuses on children, changes relating to social distancing are affecting children and adults, and schools and employment. Regarding prospects for work opportunities in a difficult economy, one study from the UK [82] assessed 78 individuals with mental handicaps, who reported that the most essential flexible working opportunity to help them work efficiently was a safe and quiet place to go when overwhelmed. Data for that study were actually collected in summer 2019, but the results were discussed in the context of the pandemic.…”
Section: Perspectivesmentioning
confidence: 99%